1987
DOI: 10.1149/1.2100708
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Cubic SiC Single‐Crystal Films on Si

Abstract: Morphological and electrical characterization results are presented for cubic SiC films grown by chemical vapor deposition on single-crystal Si substrates. The films, up to 40 ~m thick, were characterized by optical microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), electron channeling, surface profilometry, and Hail measurements. A variety of morphological features observed on the SiC films are described. Electrical measurements showed a decrease in the electron mobility w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(56 citation statements)
references
References 21 publications
4
52
0
Order By: Relevance
“…Powell et al [16] A single precursor containing both silicon and carbon can also be used in CVD process. Steckl et al [18] have successfully investigated the growth of 3C-SiC on Silicon substrate using silacyclobutane (SCB) at temperatures as low as 800 o C. Kunstmann et al [19] have reported the growth of 3C-SiC films using methyltrichlorosilane (Ch 3 SiCl 3 ) at temperature around 1200 o C.…”
mentioning
confidence: 99%
“…Powell et al [16] A single precursor containing both silicon and carbon can also be used in CVD process. Steckl et al [18] have successfully investigated the growth of 3C-SiC on Silicon substrate using silacyclobutane (SCB) at temperatures as low as 800 o C. Kunstmann et al [19] have reported the growth of 3C-SiC films using methyltrichlorosilane (Ch 3 SiCl 3 ) at temperature around 1200 o C.…”
mentioning
confidence: 99%
“…A typical APCVD reactor is comprised of a cooled wall chamber, reactive gas inlet, exhaust port, a substrate susceptor centrally positioned in the reactor chamber and heating coils . During the deposition, a carbonisation process (Nishino et al, 1983;Powell et al, 1987;Zorman et al, 1995) is initially applied to a clean Si surface, followed by SiC growth using Si and C containing precursors. SiC growth rate up to several microns per hour can be achieved with the potential to be doped into N and P types.…”
Section: Atmospheric Pressure Chemical Vapour Depositionmentioning
confidence: 99%
“…However, all the SiC films show columnar microstructures with a strong preferred orientation of (111) plane. Various systems and growth procedures for CVD SiC have been reported elsewhere [13]- [16]. Material characterization has shown that CVD SiC meets the major property requirements for the microengine such as high strength and conformality.…”
Section: A Lpcvd Sic and Residual Stress Controlmentioning
confidence: 99%